The Assessment Of Root Canal Sealers Ph In The Treatment Of Periapical Inflammation Processes - An In Vitro Study - Maria Alexandra Mârțu; Liana Aminov; Silvia Martu; Maria Vataman (Romanian Society of Oral Rehabilitation, 2013)
Introduction: The endodontic treatment represents the best conservative option for irreversible endodontically affected teeth maintenance on the dental arch. Besides the rigorous mechanic-chemical treatment, in aseptic conditions, the regenerative or, on the contrary, inhibitive qualities of the root canal sealer on the periradicular tissue play an important role in the long-term success of the treatment. The aim of the study The object of this study consisted in analysing the pH values of frequently used root canal sealers in the endodontic treatment, to make a series of correlations with their therapeutically indications. Materials and Methods We tested the following root canal sealers: AH-26 (De Trey), ZOE, Pulpispad (Spad, Dijon), Sealapex (Kerr), Endomethasone (Septodont), Endospad (Spad, Dijon). The materials were prepared according to the producer indications. The pH recordings were made on different time points: immediately after the preparation, after 24 hours, after a week and after two weeks. Results Our data analysis revealed a variation of the pH values of the 6 root canal sealers and differences in their pH values on different time recordings. The highest values were presented by Sealapex; in the alkaline values order, this was followed by Endomethasone and Endospad. The lowest pH values, to acid zones, were recorded from AH-26, ZOE and Pulpispad. Conclusions The presence in the root canal of an alkaline pH sealer ensures an additional opportunity for the infection control and tissue regeneration of the periradicular tissue. Due to this property, the root canal sealers that have calcium hydroxide in their composition are used more and more frequently.